Peran Editor Video Dalam Produksi Program Sembang Malam di Ceria TV Pekanbaru - Edison Edison; Reski Pulpi Tambes (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2019)
AbstactMass communication must be adjacent to gatekeeper, referred to as gatekeeper in an assignment i.e. the person in charge of selecting, choosing, changing, responsible later on to a will be broadcast to audiences. At CeriaTV Pekanbaru Video Editor is the role holder of gatekeeper, because the video editor in CeriaTV Pekanbaru that will answer the results of the editing later and the creativity of an editor can add the selling value of a program that is edited and presented later to the audience. CeriaTv Pekanbaru still has a shortage of human resources, then the production Director, the documentation division can concurrently become an editor. The research aims to find out how the video Editor role in the production of Sembang Malam program at CeriaTV Pekanbaru. The subject of this study is CeriaTv Pekanbaru and the object of this research is the role of editors in the production of a Sembang Malam program at CeriaTV Pekanbaru. This research uses qualitative descriptive research methods. The results of the editor's role through the first three stages, the first offline editing stage, at this stage an editor can play a role in shooting with a cameraman whose goal is to know the picture during the editing process later, and data checking. Further more the online editing stage, at this stage an editor checks equipment on the editing equipment, has its own notes for editing (according to the script), content and video visuals, editors must have the creativity issued When content editing and video visuals take place. The last stage is mixing (merging between sound and video), at this stage the sound and video must be balanced and at this stage also there are additional sounds such as sound effect, and backsound if needed. From these three stages, an editor can produce programs, both and interestingly the program is in the editor and creativity of the editors package the program, hence the editor is very important to manage the program that will be aired on audiences. Talk show-based Sembang Malam programmes that cover the hottest things, as well as inviting guest stars that inspire, from communities and individuals.